Immunohistochemical Analysis of E-Cadherin Expression in Pleomorphic Adenoma and Mucoepidermoid Carcinoma of Salivary Glands - Atarbashi Moghadam, Saedeh; Pourmahdi, Mahdi; Gholamian, Mahdi; Pedram, Hootan; Atarbashi Moghadam, Fazeleh (Journal of Dental School, 2020)
Objective: E-cadherin is a classic cadherin that plays a key role in epithelial cell adhesion. This protein is being referred to as the suppressor of proliferation and invasion. Limited studies have investigated E-cadherin expression in salivary gland neoplasms. This study sought to assess the expression of E-cadherin and its possible role in progression and invasion of salivary gland neoplasms. Methods: In this retrospective cross-sectional study, 15 samples of pleomorphic adenoma (PA) and 9 samples of mucoepidermoid carcinoma (MEC) were immunohistochemically stained for evaluation of E-cadherin expression. Degree of staining was calculated as the percentage of positively stained cell membranes out of a minimum of 1000 neoplastic cells. Results: In normal salivary gland specimens, intense membrane staining was observed around the acinar mucous and serous cells as well as the ductal cells. Myoepithelial cells were negative. In PA, intense staining was noted along the membrane of attached cells forming the ducts, islands, cellular cords and cellular sheets but the stromal myoepithelial cells were negative. In MEC, epidermoid and intermediate cells showed intense membrane staining. Mucous cells also showed membrane staining. After statistical analysis, the percentage of positive cells was found to be 82.56±11.66 and 67.4±7.24 in MEC and PA, respectively. This difference was not statistically significant (P>0.05). Conclusion: E-cadherin expression was not a suitable marker for differentiation of PA from MEC. It was only correlated with cell phenotype.